Analyzing outcomes for peripheral versus central administration of vasopressors: A narrative review - Jack Dryden; Jose Navas-Blanco (Saudi Journal of Anaesthesia)
There is an emerging body of evidence to suggest that the peripheral administration of vasopressors is safe and effective in many clinical contexts and often superior to central administration. Vasopressors are a class of medications used to create vasoconstriction in patients with shock to increase systemic arterial blood pressure and tissue perfusion. Certain clinical circumstances require the use of these vasoactive drugs immediately for which the need to administer these drugs peripherally becomes paramount, although controversial. The authors present a narrative review dedicated to describing the current practice of the route of administration of vasopressors, comparing peripheral versus central administration, and explaining the advantages and drawbacks of each route as well as potential complications associated with them.